Revision of the Eurybrachidae XVIII. The Australian genus Olonia Stål, 1862: Four new species, new records and biological data (Hemiptera: Fulgoromorpha) - Constant, Jérôme (European Journal of Taxonomy, 2024)
Four new species of the Australian genus of Eurybrachidae (Hemiptera, Fulgoromorpha) Olonia Stål, 1862 are described from northern Queensland: O. albomarginata sp. nov., O. aschei sp. nov., O. jackiei sp. nov. and O. lindae sp. nov. Host plants and natural history data are documented and additional new records provided for O. guillaumei Constant, 2018, O. hochae Constant, 2018, O. picea Kirkaldy, 1906, O. rubicunda (Walker, 1851) and O. soulierae Constant, 2018. Trophobiosis is recorded for the first time in the genus, between a female of O. hochae and ants of the genus Camponotus Mayr, 1861 (Hymenoptera, Formicidae), representing the second record of trophobiosis in Australian Eurybrachidae. The male terminalia of the new species are illustrated and photographs of collection and live specimens, distribution maps, biological data and an identification key are provided. The genus Olonia currently contains sixteen species.